Questionnaire survey of California consumers' use and rating of sources of health care information including the Internet - Pennbridge, J; Moya, R; Rodrigues, L (The Western journal of medicine, 1999)
OBJECTIVE: To understand how Californians use and rate various health information sources, including the Internet. RESEARCH DESIGN: Computer-assisted telephone interviews through which surveys were conducted in English or Spanish. SUBJECTS: A household sample generated by random digit dialing. The sample included 1007 adults (18+), 407 (40%) of whom had access to the Internet. MAIN OUTCOME MEASURES: Past health information sources used, their usefulness and ease of use; future health information sources, which are trusted and distrusted; and concerns about integrating the Internet into future health information seeking and health care behaviors. RESULTS: Physicians and health care providers are more trusted for information than any other source, including the Internet. Among those with Internet access, a minority use it to obtain health information, and a minority is "very likely" to use e-mail to communicate with medical professionals or their own doctors and nurses, to refill prescriptions, or to make doctor appointments. Also, most of those with Internet access are "unlikely" to make their medical records available via the Internet, even if securely protected. CONCLUSIONS: The public, including frequent Internet users, has major concerns about the confidentiality of electronic medical records. Legislation may not assuage these fears and a long-term, open and collaborative process involving consumers and organizations from all the health care sectors may be needed for full public assurance.